If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2x + -3) + -2(x + 4) = 0 Reorder the terms: 5(-3 + 2x) + -2(x + 4) = 0 (-3 * 5 + 2x * 5) + -2(x + 4) = 0 (-15 + 10x) + -2(x + 4) = 0 Reorder the terms: -15 + 10x + -2(4 + x) = 0 -15 + 10x + (4 * -2 + x * -2) = 0 -15 + 10x + (-8 + -2x) = 0 Reorder the terms: -15 + -8 + 10x + -2x = 0 Combine like terms: -15 + -8 = -23 -23 + 10x + -2x = 0 Combine like terms: 10x + -2x = 8x -23 + 8x = 0 Solving -23 + 8x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '23' to each side of the equation. -23 + 23 + 8x = 0 + 23 Combine like terms: -23 + 23 = 0 0 + 8x = 0 + 23 8x = 0 + 23 Combine like terms: 0 + 23 = 23 8x = 23 Divide each side by '8'. x = 2.875 Simplifying x = 2.875
| -8x^2+8x+9=0 | | -13-(-10)= | | 330+25h=455 | | Y(-2)=5(-2)(-2)-7 | | 15-19= | | (-5)(-14)= | | 3x+26=11x-40 | | y(1)=4(1)(1)-6(1)+3 | | 8x-24=74 | | 6c+20c= | | (12x+5)+(7x-6)= | | y(0)=5(0)(0)-7 | | x^3+4x^2-5x+2=0 | | 5.7x-2=4.7x | | -6=-10 | | x^3+x^2+x=3 | | y(1)=7(1)(1)-3(1)+1 | | 8x-5y=4y | | (-2)+w=-9 | | x+-9=-15 | | 4(-9x+5)=11(7x-6) | | -6=11+j | | 5(X+RY)=20 | | 8=h-3 | | 551+32j=615 | | b+10=2 | | 4.2x=-4(0.6x-1.2) | | (-9)+r=17 | | [2x-5]=x+4 | | 10y=2x-6 | | y(-1)=3(-1)+3 | | 4(9x+5)=11(7x-6) |